Kinetic Studies of Electrowinning and Electrorefining of Copper in Presence of Mono Carboxylic Acids - M. El-Kashlan, Howaida (Asian Journal of Chemistry, 2011)
The effect of some acids such as acetic acid, phenyl acetic acid and formic acid on the rate of electrowinning and electrorefining of copper were studied using copper anode and lead anode. It is found that the rate of deposition decreases by adding organic acids and depend on the type of acids. The rate of deposition increases by raising temperature. The ability of different acids to decrease the rate of deposition decreases in order phenyl acetic acid > acetic acid > formic acid.